2009
DOI: 10.1159/000260135
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Effects of a Neonatal High-Protein Diet in Low-Birth-Weight Piglets Used as a Model of Intrauterine Growth Restriction

Abstract: Background: Although full-term infants suffering intrauterine growth restriction (IUGR) are routinely fed high-protein (HP) formulas to ensure catch-up growth, the effects of HP intake are poorly understood. An IUGR piglet model provides an opportunity to investigate these effects. Methods and Results: Twelve IUGR piglets were artificially fed HP formulas (50% more protein in comparison to sow milk) from the 2nd day of life (d2) until d28. Unexpectedly, all HP piglets developed poor growth, severe hypotonia an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 47 publications
1
30
1
Order By: Relevance
“…Thirty four cross-bred full-term IUGR piglets were obtained from the experimental herd of Institut National de la Recherche Agronomique (INRA, Saint-Gilles, France). They were chosen at birth, as described previously (25), so that their mean birth body weight (BW) was 0.92 Ϯ 0.02 kg (i.e., around the 10th percentile of the herd birth weight). Both entire male and female piglets were allowed to suckle colostrum from their dams for the first 2 days.…”
Section: Animals and Dietsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thirty four cross-bred full-term IUGR piglets were obtained from the experimental herd of Institut National de la Recherche Agronomique (INRA, Saint-Gilles, France). They were chosen at birth, as described previously (25), so that their mean birth body weight (BW) was 0.92 Ϯ 0.02 kg (i.e., around the 10th percentile of the herd birth weight). Both entire male and female piglets were allowed to suckle colostrum from their dams for the first 2 days.…”
Section: Animals and Dietsmentioning
confidence: 99%
“…Pairs of littermates of the same sex were then randomly assigned to one of the two dietary groups. They received milk replacers formulated to provide an adequate protein (AP; 1.05 g of protein/100 kJ mimicking sow's milk) or a high protein (HP; 1.5 g of protein/100 kJ) protein supply (Table 1; 25). After separation from their dam, they were placed individually in incubators (33°C, 60% humidity) and were bottle-fed every 2 h from 0700 to 2300 and once during the night at 0300 from day 2 to day 7 (25).…”
Section: Animals and Dietsmentioning
confidence: 99%
See 2 more Smart Citations
“…2008; Jamin et al. 2010). In a similar study design, HP feeding of IUGR piglets has been shown to induce metabolic and electrolyte disturbances mimicking refeeding syndrome, a surrogate of active anabolic response to HP intake (Jamin et al.…”
Section: Discussionmentioning
confidence: 99%